Father's Role in Exclusive Breastfeeding in Developing Countries: Scoping Review - Sari, Siti Nurul Fadhilah; Astuti, Andari Wuri (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
The father is the closest person after the baby's mother, who plays a role in exclusive breastfeeding. The interventions of dads attempt to improve breastfeeding knowledge, positive attitudes, and fathers' engagement in providing practical, physical, and emotional support to mothers, which can improve breastfeeding behaviors. The purpose of this study is to map current information about the role of fathers in exclusive breastfeeding in developing countries by including relevant sources of evidence from each article that has been found. The research method uses a Scoping review with the Arkey and O'Malley approach. It consists of 5 steps, namely: (1) identifying each scoping review question, (2) identifying relevant articles, (3) selecting articles, (4) charting data (5) compiling, summarizing and reporting results. Article search uses three databases, PubMed, ScienceDirect and Wiley, published between 2018-2022. Keywords used in the search process are (Father Role* OR Partner Role*) AND (Exclusive Breastfeeding* OR Lactation* OR Breast Milk*). There are 14 articles found, including several developing countries from various continents, nine articles from Thailand, Vietnam, Iran, India, Philippines, and China from the Asian continent, and five articles from the countries Tanzania, Ethiopia, and South Africa from the African continent. The results of the study show that the father's role in exclusive breastfeeding in developing countries is to provide emotional support, practical support and informational support so that mothers have a greater chance of producing breast milk more effectively. Husband’s support towards breastfeeding mothers positively affects the mother's psychological condition and success, especially in exclusive breastfeeding. The next author is expected to help make the policy if health workers are required, especially the policy for husbands to be involved in giving counseling while accompanying their wives in health facilities.